Ancient Harappa in 3-D - Belcher, Wayne (1997)
[Dt.:] Diese Webeite zeigt dreidimensionale Darstellungen der Ausgrabungshügel sowie der räumlichen und architektonischen Gestaltung von Harappa, einer der wichtigsten Stätten der Indus-Kultur. Die Animationen wurden von Wayne Belcher erstellt und beruhen auf Ausgrabungsergebnissen von M. S. Vat in den 1920er Jahren und des Harappa Archaeological Research Project in den 1980er und 1990er Jahren. - [Engl.:] This webpage contains a computer visualization of the ancient Indus Valley city of Harappa in contemporary Punjab (Pakistan), which was one of the most important site of the Indus Valley. It is based on M. S. Vat's excavations at the site in the late 1920s and the Harappa Archaeological Research Project (HARP) excavations in the 1980s and 1990s.